Non-Invasive Detection of Early Metabolic Left Ventricular Remodeling in Systemic Hypertension - Hamirani, Yasmin S (Cardiology, 2015)
OBJECTIVES: Hypertension (HTN) is a common cause of left ventricular hypertrophy (LVH). Sustained pressure overload induces a permanent myocardial switch from fatty-acid to glucose metabolism. In this study we tested the hypothesis that metabolic remodeling, characterized by increased myocardial glucose uptake precedes structural and functional remodeling in HTN induced LVH. METHODS: We recruited 31 patients: 11 with HTN only, 9 with HTN and LVH, and 11 normotensive controls without LVH. Transthoracic echocardiography was performed to assess left ventricular (LV) function, LV mass, LV wall thickness, and LV diastolic function. PET imaging was performed and the rate of myocardial 2-deoxy-2-[(18)F]fluoro-D-glucose uptake, Ki, was determined using a 3-compartment kinetic model. RESULTS: The mean Ki values were significantly higher in HTN patients compared to HTN with LVH (p<0.001) and control (p=0.003) patients. The unexpected decrease in Ki with LVH may be secondary to a decreased Ki with diastolic dysfunction (DD), 0.039±0.032 versus 0.072±0.013, p=0.004. Also, there was a significant stepwise decrease in Ki with increasing DD grade(p=0.04). CONCLUSION: Glucose metabolic remodeling is detectable in hypertensive patients before the development of LVH. Furthermore, lower glucose uptake rates are observed in patients with DD. The mechanism for this last finding requires further investigation.